Improved Integrated Modulation Strategy for Dual-Parallel Three-Level Inverters to Suppress Leakage Currents - Park, Jun Hyeok; Choi, Hye Won; Lee, Kyo Beum (IEEE Transactions on Power Electronics, 2024)
This article proposes an improved integrated modulation strategy of dual-parallel three-level inverters to suppress leakage current. Dual-parallel three-level inverters are widely used in several applications, such as in photovoltaic systems, wind power generation, and motor drive systems to increase the power capacity. The current ripple of each inverter appears greater on the load side due to the parallel operation of inverters. Thus, asynchronous modulation methods, such as interleaved or integrated modulation, have been proposed to improve the output current quality of three-level inverters. These asynchronous modulations generate a significant leakage current due to limited common-mode voltage (CMV) reduction. In this article, the proposed five-level reduced leakage current space vector modulation (RLC SVM) strategy adopts a switching sequence that lowers the CMV frequency. The proposed modulation solves problems such as insulation breakdown and electromagnetic interference by significantly suppressing the leakage current of the existing integrated modulation. Thus, the five-level RLC SVM method reduces the CMV, ZSCC, and output current distortion, as well as the leakage current. The feasibility and effectiveness of the proposed modulation method are verified based on simulations and experiments.
Keywords: Common mode voltage; Inverter; Modulation methods; Modulation strategy; Photovoltaic systems; Power motors; Pulsewidth modulations (PWM); Support vectors machine; Three-level inverters; Wind power generation; Dual-parallel three-level inverter; five-level inverter; leakage current; reduced common-mode voltage